Photodegradation of polycaprolactone/poly(vinyl chloride) blend - Christensen, P. A.; Egerton, T. A.; Martins-Franchetti, S. M. [UNESP]; Jin, Changqing; White, Jr. (Elsevier B.V., 2008)
The photodegradation of a 1:1 w/w blend of polycaprolactone and poly(vinyl chloride) has been studied by following carbon dioxide emission during UV exposure. Similar measurements were performed for polycaprolactone and poly(vinyl chloride) homopolymers which were prepared and irradiated in the same way. It was found that the blend gave lower CO2 emission than either of the two homopolymers, indicating that the interaction of the two components in the blend provided a beneficial reduction of photodegradation. It is therefore deduced that the detailed morphological characteristics of the blend have a controlling influence over the photo-oxidation. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: photodegradation; PVC; PCL; blend